2016
DOI: 10.1037/pha0000079
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive enhancement or impairment? A systematic meta-analysis of prescription stimulant effects on processing speed, decision-making, planning, and cognitive perseveration.

Abstract: Increasing numbers of adults, particularly college students, are misusing prescription stimulants primarily for cognitive/academic enhancement, so it is critical to explore whether empirical findings support neurocognitive benefits of prescription stimulants. Previous meta-analytic studies have supported small benefits from prescription stimulants for the cognitive domains of inhibitory control and memory; however, no meta-analytic studies have examined the effects on processing speed or the potential impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 88 publications
2
40
0
Order By: Relevance
“…Nonetheless, findings from this study are notable in that significant and small effects of amphetamine were found to benefit processing speed (Marraccini et al, in press). …”
Section: Processing Speedmentioning
confidence: 65%
See 4 more Smart Citations
“…Nonetheless, findings from this study are notable in that significant and small effects of amphetamine were found to benefit processing speed (Marraccini et al, in press). …”
Section: Processing Speedmentioning
confidence: 65%
“…Preliminary findings from a meta-analysis examining the neurocognitive effects of prescription stimulants cognitive flexibility (Marraccini et al, in press), however, did not support Advokat’s (2010) conclusions about impairments of cognitive flexibility. Although limited by a small number of studies ( k = 6), results suggested that amphetamine and methylphenidate did not result in significant effects on cognitive perseveration.…”
Section: Cognitive Controlmentioning
confidence: 94%
See 3 more Smart Citations